2009
DOI: 10.2337/db08-1070
|View full text |Cite
|
Sign up to set email alerts
|

Heat Treatment Improves Glucose Tolerance and Prevents Skeletal Muscle Insulin Resistance in Rats Fed a High-Fat Diet

Abstract: OBJECTIVE-Heat treatment and overexpression of heat shock protein 72 (HSP72) have been shown to protect against high-fat diet-induced insulin resistance, but little is known about the underlying mechanism or the target tissue of HSP action. The purpose of this study is to determine whether in vivo heat treatment can prevent skeletal muscle insulin resistance. RESEARCH DESIGN AND METHODS-MaleWistar rats were fed a high-fat diet (60% calories from fat) for 12 weeks and received a lower-body heat treatment (41°C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
228
4
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(260 citation statements)
references
References 50 publications
26
228
4
2
Order By: Relevance
“…Incidentally, a previous study reported that a high-fat diet feeding also leads to mitochondrial biogenesis in skeletal muscle 21) . However, in another high-fat diet study, heat stress canceled mitochondrial biogenesis in rat skeletal muscle (hindlimbs hot bathing, 41ºC, 20 min) 5) , indicating that the additive effects of heat stress on mitochondrial adaptations are not universally observed. Thus, it could be notable that there are additive effects of heat stress on exercise training-induced mitochondrial biogenesis.…”
Section: Brief History Of Research On Heat Stress In Skeletal Musclementioning
confidence: 96%
See 1 more Smart Citation
“…Incidentally, a previous study reported that a high-fat diet feeding also leads to mitochondrial biogenesis in skeletal muscle 21) . However, in another high-fat diet study, heat stress canceled mitochondrial biogenesis in rat skeletal muscle (hindlimbs hot bathing, 41ºC, 20 min) 5) , indicating that the additive effects of heat stress on mitochondrial adaptations are not universally observed. Thus, it could be notable that there are additive effects of heat stress on exercise training-induced mitochondrial biogenesis.…”
Section: Brief History Of Research On Heat Stress In Skeletal Musclementioning
confidence: 96%
“…Therapeutic effects of heat stress on insulin resistance have been reported in type 2 diabetes of rodents (hindlimb hot bathing, 41ºC, 20 min) 5) and patients (Hot tub bathing, 37.8-41.0ºC, 30 min/ day, 6 days/week, 3 weeks) 6) , mediated by up-regulated glucose uptake in skeletal muscles, based on a mechanistic study investigating isolated skeletal muscle (42ºC, 30 min) 7) . In addition to glucose metabolism, several lines of evidence demonstrated various adaptabilities of mitochondria-centered oxidative metabolism by heat stress.…”
Section: Brief History Of Research On Heat Stress In Skeletal Musclementioning
confidence: 99%
“…HSPs act as molecular chaperones, and the expression can increase in response to physical and chemical stressors as well as oxidative stress. Several laboratories (21,35) have demonstrated that induction of HSPs by heat treatment can protect against obesity-related insulin resistance and that an increased expression of HSP70 and HSP25 plays a significant role in protecting SM from the development of age-related insulin resistance (20). Moreover, the small HSPs especially protect against ROS and stress situations such as ATP depletion (1).…”
Section: E500mentioning
confidence: 99%
“…Despite the lack of proper controls and its exploratory nature, the credibility of this early report has been substantiated by similar studies from animal models of DM. For example, whereas high-fat diet evoked significant hyperglycemia, hyperinsulinemia, insulin insensitivity, glucose intolerance as well as JNK and IKKactivation in skeletal muscles in rodents, weekly heat therapy upregulated HSP70 which paralleled an apparent attenuation of these metabolic characteristics (Chung et al, 2008;Gupte et al, 2009b). Chung et al further demonstrated that targeted overexpression of HSP70 in mouse skeletal muscles mimicked the effects of heat therapy in preventing fat-induced JNK phosphorylation, insulin resistance and fat deposition, suggesting that HSP70 might mediate the beneficial effects afforded by heat therapy (Chung et al, 2008).…”
Section: Hsp Inhibits Inflammation and Stress Kinasesmentioning
confidence: 99%